Evaluating Mending Mamre: An Animal Welfare Intervention - Rabier, Camille (Organisational Psychology, 2020)
The need to improve animal welfare and control companion animal populations is necessary for South Africa, especially in impoverished communities lacking resources and education to care for their pets responsibly. These programmes are often multi-dimensional in nature and aim to improve animal welfare in different ways. Sterilisation is often the first step but is not enough. Consequently, education is often used in combination, to teach responsible pet care and ownership to pet owners. By increasing their understanding and knowledge of animals it is hoped that the pets’ overall quality of life and welfare improve. The following dissertation presents the findings of an evaluation conducted for the Mending Mamre Mass Education and Sterilisation Programme. This programme had four components: surgical sterilisation of pets and feral cats, basic veterinary care, education sessions and the rehoming of stray dogs. Three evaluations were performed (as requested by the clients): a programme theory evaluation of the education sessions, a process evaluation to understand why some residents refused sterilisation and an outcome evaluation to measure if the pets’ living conditions and body scores had changed 16 months after the programme. Overall, the results of the programme theory evaluation demonstrated that: the activities and outcomes of the education sessions were consistent with similar programmes but the two causal pathways underlying the programme are not plausible. The results of the process evaluation highlighted that the most common reason why pet owners refused sterilisation was due to fear. Finally, the results of the outcome evaluation indicated mixed results; with an increase observed in the pets’ physical wellbeing but an overall decrease observed in their quality of living conditions. With the results, the evaluator was able to make recommendations to the client and highlight considerations for programme improvement. Overall this study contributes to the paucity of research on evaluations of animal welfare interventions at the community level.